A case study in flux balance analysis: Lysine, a cephamycin C precursor, can also increase clavulanic acid production - Cavallieri, André Pastrelo [UNESP]; Baptista, Amanda Salvador [UNESP]; Leite, Carla Andréa [UNESP]; Araujo, Maria Lucia Gonsales da Costa [UNESP] (Elsevier, 2016)
Streptomyces clavuligerus is an excellent model for studying complex relationships involved in the biosynthesis of secondary metabolites. Despite the fact that several studies have investigated the mechanisms pertaining to the biosynthesis of two bioactive compounds produced by S. clavuligerus, cephamycin C (CephC) and clavulanic acid (CA), few have focused on metabolic flux analyses of this microorganism. It was proposed a novel representative metabolic model for S. clavuligerus addressing the simultaneous production of CephC and CA using flux balance analysis methodology (FBA). Although both are synthesized via different pathway, flux analysis showed that the production of these bioactives are connected. CephC production showed high dependency on N metabolism while CA production is more related with C metabolism. Adding lysine plus maltose increased CA, an interesting outcome since lysine is a CephC precursor. Notwithstanding, it was possible to propose a mechanism for this behavior by means of flux analysis. Furthermore, the results suggest that ATP yield maximization is the objective function that best suits the conditions under investigation.
Keywords: Antibiotic; Filamentous bacteria; Flux balance analysis; Growth kinetics; Lysine; Physiology